Imaging the voluntary actor : an exploration of the nature of the voluntary actor and of the relationship between the voluntary actor and voluntary action - O'Regan, Andrew (Trinity College (Dublin, Ireland). Trinity Business School, 2008)
The emerging academic field of voluntary action, nonprofit or third sector studies is a multi-disciplinary, social science field that addresses the phenomenon of voluntary action as an organised endeavour in society. In this context, this dissertation examines the functioning of the individual as social actor. Specifically, the following questions are addressed: What is the nature of the voluntary actor? And, as an extension of this question, what is the nature of the relationship between the voluntary actor and voluntary action?
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin